(untitled) (Research, Society and Development, 2021)
This scope review aims to map food literacy intervention studies, according to the economic classification of the origin country. Using guidelines from The Joanna Briggs Institute (2020), a search in eight databases was performed in addition to gray literature. The study involved adult audiences, publications from various countries and in any language. The selection process and data extraction from the studies were carried out by independent researchers. Inclusion criteria were met by 20 studies, published between 2008 and 2020. Most interventions are developed in higher-income countries, with two publications in middle-income countries and no publications in low-income countries. This review both highlighted the need for discussions on nomenclatures and concepts associated with food, nutritional and scientific literacy, as well as for discussions on the best designs to assess intervention results, the content priorities and the best intervention time.